Atypical antipsychotic drug use and falls among nursing home residents in Winnipeg, Canada. (3rd November 2014) - Bozat‐Emre, Songul; Doupe, Malcolm; Kozyrskyj, Anita L.; Grymonpre, Ruby; Mahmud, Salaheddin M.
<x xml:space="preserve">Abstract</x> Objective The purpose of this study is to assess whether atypical antipsychotic drug (AAD) use is associated with increased risk of falling among older (≥65 years) nursing home (NH) residents. Methods We conducted a nested case–control study using Resident Assessment Instrument Minimum Data Set 2.0 (RAI‐MDS©) for NHs to identify falls, and population‐based administrative healthcare databases to measure drug use and other study covariates. Cases (n = 626) were NH residents in Winnipeg, Canada, who had a fall between 1 April 2005 and 31 March 2007, and were matched to four controls on age, sex, and length of NH stay (n = 2388). Results While the odds of falling were statistically greater for AAD users versus nonusers (OR = 1.6, 95% CI 1.1–2.3), this association was type and dose dependent. Compared to nonusers, the odds of falling were greater for high‐dose (>150 mg/day) quetiapine users and for high‐dose (>2 mg/day) risperidone users. On the other hand, olanzapine (regardless of dose), low‐dose quetiapine, and low‐dose risperidone use were not associated with increased fall risk. Furthermore, the effect of AAD use, in general, on the risk of falling was significantly greater for people with wandering problems (OR = 1.8, 95% CI 1.1–3.1). Conclusions Our findings suggest greater risk of falling with high‐dose quetiapine use and with high‐dose risperidone use among NH residents. In addition, the effect of AAD use was greater for people who frequently wander. Further research is needed to confirm these findings, and to address other important unanswered questions about the safest dose and duration of AAD use. Copyright © 2014 John Wiley & Sons, Ltd.